Cyclic loading response of footing on multi-layered rubber-soil mixtures - Moghaddas Tafreshi, S.N.; Joz Darabi, N.; Dawson, Andrew (Techno Press, 2018)
This paper presents a set of results of plate load tests that imposed incremental cyclic loading to a sandy soil bed containing multiple layers of granulated rubber-soil mixture (RSM) at large model scale. Loading and unloading cycles were applied with amplitudes incrementally increasing from 140 to 700 kPa in five steps. A thickness of the RSM layer of approximately 0.4 times the footing diameter was found to deliver the minimum total and residual settlements, irrespective of the level of applied cyclic load. Both the total and residual settlements decrease with increase in the number of RSM layers, regardless of the level of applied cyclic load, but the rate of reduction in both settlements reduces with increase in the number of RSM layers. When the thickness of the RSM layer is smaller, or larger, settlements increase and, at large thicknesses may even exceed those of untreated soil. Layers of the RSM reduced the vertical stress transferred through the foundation depth by distributing the load over a wider area. With the inclusion of RSM layers, the coefficient of elastic uniform compression decreases by a factor of around 3-4. A softer response was obtained when more RSM layers were included beneath the footing damping capacity improves appreciably when the sand bed incorporates RSM layers. Numerical modeling using “FLAC-3D” confirms that multiple RSM layers will improve the performance of a foundation under heavy loading.